Antibiotic Resistance Among Coliform and Fecal Coliform Bacteria Isolated from Sewage, Seawater, and Marine Shellfish - Cooke, Marylyn D. (1976)
Seawater and shellfish samples collected in the vicinity of a marine sewage outfall were examined for the incidence of antibiotic resistance among coliform and fecal coliform bacteria over a 2-year period. Seventy percent or more of these two groups of bacteria from both sources were resistant to one or more antibiotics. Forty-five percent of the isolates resistant to streptomycin or tetracycline were capable of transferring all or part of their resistance pattern to an antibiotic-susceptible strain of Escherichia coli K-12.